Common knowledge of the second kind - Bella, David (Journal of business ethics, 1989)
Although most of us “know” that human beings cannot and should not be replaced by computers, we have great difficulties saying why this is so. This paradox is largely the result of institutionalizing several fundamental misconceptions as to the nature of both trustworthy “objective” and “moral” knowledge. Unless we transcend this paradox, we run the increasing risks of becoming very good at counting without being able to say what is worth counting and why. The degree to which this is occurring is the degree to which the computer revolution is already over — and the degree to which we human beings have lost.